Metasurface-Based Wideband CP Antenna Array Using Hybrid Coupler for 5G Mid-band Applications - Nathapat Supreeyatitikul; Titipong Lertwiriyaprapa; Chuwong Phongcharoenpanich (My University, 2023)
This paper proposes the lemon-shaped metasurface (MTS)-based wideband circularly polarized (CP) antenna array using hybrid coupler for mid-band wireless communications. The proposed MTS-based CP antenna array includes two-stack layers of FR-4 substrate: upper-stack and lower-stack substrates. The upper-stack substrate contains quadri clusters of $4\times 4$ MTS cells. The lower-stack substrate consisted of four slots as the ground plane and hybrid couple as the feed network. Besides, the MTS elements and hybrid couple feed network function as polarization conversion. The proposed MTS-based CP antenna array for 5G mid-band spectrum (center frequency at 4 GHz) achieves simulated IBW of 41.25% (3.35–5 GHz) and ARBW of 21.25% (3.68–4.53 GHz). The simulated maximum gain at 3.9 GHz is 9.1 dBic. The radiation characteristic is right-hand circular polarization radiation.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Millimeter-Wave Propagation and Modeling